Some Aspects of Volatile Fission Product Behaviour and Associated Population Dose in Postulated Accidents - Yuen, Peter S.L. (My University, 1978)
In this report, models, equations, and methodology useful in the analysis of remval of radioactive ionedine in the form of elemantal iondone and methyl iodide from the reactor containment by sprays and deposition after a postulated Loss of Coolant and Loss of Emergency Core Coolant (LOC/LOECC) accident are discussed.
Also discussed are applicable methodology useful in the estimation of population dose as a result of the escape of radioactive iodine and noble gases out of the containment after such a postulated accident. A computer program POPDOSE was written to estimate population dose based on this methodology.
Results of analysis and details of POPDOSE are not important for the purposes of this report and are not included here.
Title: Some Aspects of Volatile Fission Product Behaviour and Associated Population Dose in Postulated Accidents, Author: Peter S.L. Yuen, Location: Thode